Proof of Participation in the Crime of Theft - Br. Sitepu, Asmita; Azhali Siregar, Mhd. (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study examines and reviews participation (deelneming) which includes the form of participation/involvement of a person, both psychologically and physically, by committing an act so that a criminal act occurs. The crime of participation is regulated in Article 55 of the Criminal Code, which means that there are two or more people who commit a criminal act. This study is a type of normative research using secondary legal sources and using qualitative descriptive analysis. The results of this study are that the forms of participation crimes can be divided into two parts, namely: first, the perpetrator consisting of: the perpetrator (pleger), the one who orders it (doenpleger), the one who participates (madepleger) and the advocate (uitlokker); second, the assistant consisting of: the assistant at the time the crime was committed and the assistant before the crime was committed.